Composite adsorbent for improving phosphate fire-resistant oil performance and use method

By using a composite adsorbent composition of deacid, dehydration, decolorization and defoaming curing agent in phosphate anti-fuel oil, the problem of not being able to optimize multiple performances simultaneously in the prior art is solved, and the quality of oil products and operation stability is achieved Increased performance and reduce operating costs.

CN119140062APending Publication Date: 2024-12-17HUANENG GANSU ENERGY DEV CO LTD XIGU BRANCH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411417809.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing phosphate anti-fuel adsorbents cannot simultaneously optimize the color, acid value, resistivity, moisture and foam characteristics of the oil product. The uneven dispersion of the defoamer leads to an increase in the risk of unit operation, and the complexity of traditional adsorbent devices increases maintenance costs.

Method used

Compound adsorbent compositions, including deacidification, dehydration, decolorization and defoaming curing agents, are added to the anti-fume oil after drying and mixing, and use materials such as silicon-aluminum adsorbents, molecular sieves, activated carbon, etc. to improve the adsorption effect and improve the dispersion of defoaming agents. sex.

Benefits of technology

Effectively reduce the color, acid value and moisture of phosphate fuel resistance, improve resistivity and defoaming ability, extend the service life of oil products, reduce operating costs, and improve unit operation stability and economicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005079921420000071
    Figure BDA0005079921420000071
  • Figure BDA0005079921420000081
    Figure BDA0005079921420000081
  • Figure BDA0005079921420000091
    Figure BDA0005079921420000091
Patent Text Reader

Abstract

The invention provides a composite adsorbent for improving phosphate fire-resistant oil performance and a use method, and belongs to the field of phosphate fire-resistant oil performance improvement, the composite adsorbent comprises a deacidification adsorbent, a dehydration adsorbent, a decoloration adsorbent and a defoaming curing agent, the dehydration adsorbent accounts for 20-30 wt%, and the defoaming curing agent accounts for not more than 5 wt%. The composite adsorbent can reduce the color, acid value and moisture of the phosphate fire-resistant oil at the same time, improve the electrical resistivity of the phosphate fire-resistant oil, improve the anti-foaming and de-foaming capacities of the phosphate fire-resistant oil, effectively improve the use performance of the phosphate fire-resistant oil, prolong the service life of the phosphate fire-resistant oil, save resources, reduce the cost, improve the operation and maintenance efficiency of a unit and further improve the economical efficiency and stability of operation of the generator set.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of adsorption treatment of phosphate fire-resistant oils, and in particular to a composite adsorbent for improving the performance of phosphate fire-resistant oils and a method for using the same. Background Art

[0002] Compared with mineral oil, phosphate ester flame retardant fluid has excellent flame retardant properties (autoignition point is above 530℃). As a working medium, it is widely used in the power, aviation, metallurgy and other industries, especially in the hydraulic system of the generator set regulation system. Its quality is crucial to the safe and smooth operation of the unit. During the use of phosphate ester flame retardant fluid, it will inevitably come into contact with oxygen, moisture or metal, and thus deteriorate due to oxidation or hydrolysis. The deteriorated components produced are mostly polar molecules containing hydroxyl groups, aldehyde groups, etc. When the deteriorated components in the oil accumulate too much, it will lead to a qualitative change in the performance of the oil, which is manifested as a darker color of the oil, an increase in acid value, a decrease in resistivity, and a deterioration in foam properties, which in turn threatens the safe operation of the unit.

[0003] At present, almost all domestic power plants use imported phosphate ester fire-resistant oil. However, due to the turbulent international situation, the superposition of trade barriers and the continuous increase of import tariffs, the procurement risks and costs of imported phosphate ester fire-resistant oil for my country's power generation companies are increasing day by day. In addition, waste phosphate ester fire-resistant oil has been included in the "National Hazardous Waste List", which has greatly increased the difficulty and cost of handling waste phosphate ester fire-resistant oil. Therefore, manufacturers often use adsorbents to absorb and separate deteriorated components from oil products, so as to achieve the purpose of restoring oil performance and extending the service life of oil products.

[0004] At present, although there are many types of phosphate ester fire-resistant oil adsorbents on the market, their functions are single and they cannot simultaneously meet the processing requirements of key indicators such as color, acid value, resistivity, moisture and foam characteristics of phosphate ester fire-resistant oil, which brings many difficulties to the selection of fire-resistant oil adsorbents for manufacturers. In particular, when improving the foam characteristics of phosphate ester fire-resistant oil by adding defoamers, the defoamers are often unevenly dispersed or even agglomerated and lose their effect, which may cause "false oil level" and increase the risk of unit operation.

[0005] Oil maintenance devices based on traditional adsorbents require the installation of complex processing units, which reduces the integration of fire-resistant oil operation systems. At the same time, the complex pipelines in the oil maintenance device also increase the risks of oil leakage and oil contamination, increase the cost of personnel maintenance, repair and replacement of filter elements, and are not conducive to the safe and economical operation of the unit. Therefore, the development of new phosphate fire-resistant oil composite adsorbents and the efficient improvement of their performance have become the development direction of this field. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes a composite adsorbent for improving the performance of phosphate ester fire-resistant oil and a method of using the composite adsorbent, which can simultaneously improve the key properties of phosphate ester fire-resistant oil, such as color, acid value, resistivity, moisture and foam characteristics, and improve the dispersion effect of defoaming agent in fire-resistant oil.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a composite adsorbent for improving the performance of phosphate fire-resistant oils, comprising a deacidifying adsorbent, a dehydrating adsorbent, a decolorizing adsorbent and a defoaming curing agent, wherein the dehydrating adsorbent accounts for 20wt% to 30wt%, and the defoaming curing agent accounts for no more than 5wt%.

[0009] Preferably, the deacidification adsorbent includes a silica-alumina adsorbent, and a silica-alumina adsorbent and one or more compositions of activated alumina, activated magnesium oxide and diatomaceous earth; wherein at least a silica-alumina adsorbent is included, and when the deacidification adsorbent is a plurality of compositions, the proportion of the silica-alumina adsorbent is not less than 70wt%.

[0010] Preferably, the particle size of each component in the deacidification adsorbent is 100 μm to 150 μm.

[0011] Preferably, the dehydration adsorbent comprises a combination of one or both of molecular sieve and silica gel; the molecular sieve accounts for no less than 80 wt % of the composition.

[0012] Preferably, the decolorizing adsorbent comprises at least two compositions of activated carbon, silicon-aluminum adsorbent and activated magnesium oxide; wherein, when at least activated carbon is included, the proportion of activated carbon is not higher than 15wt%;

[0013] Or the decolorizing adsorbent is a silicon-aluminum adsorbent or active magnesium oxide.

[0014] Preferably, the size of the silica-alumina adsorbent and the activated magnesium oxide in the decolorizing adsorbent is 100 μm to 150 μm; the size of the activated carbon is 150 μm to 200 μm.

[0015] Preferably, the defoaming curing agent comprises activated carbon and a defoaming agent.

[0016] Preferably, the pore size of the outer channel of the activated carbon is not less than 2000 nm; the activated carbon is coal-based activated carbon, wood-based activated carbon or fruit shell activated carbon.

[0017] Preferably, the particle size of the defoamer is no more than 1000 nm; the defoamer is a polyether defoamer or a silicone defoamer.

[0018] In a second aspect, the present invention provides a method for using a composite adsorbent for improving the performance of phosphate fire-resistant oils, comprising the following steps:

[0019] The deacidification adsorbent, the dehydration adsorbent and the decolorization adsorbent are dried and mixed with a defoaming curing agent to obtain a composite adsorbent, and the composite adsorbent is added into the fire-resistant oil to be treated;

[0020] The preparation method of the defoaming curing agent is as follows: adding the defoaming agent to petroleum ether or anhydrous ethanol, stirring to obtain a uniformly mixed dilution; adding activated carbon with a volume of half the dilution to the dilution, after ultrasonic vibration, drying the activated carbon to obtain the defoaming curing agent.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The deacidifying adsorbent in the present invention is used to remove polar aging products in phosphate ester fire-resistant oil, prevent polar aging products from accelerating oil degradation, and improve the service life of the oil. The dehydrating adsorbent is used to remove moisture in phosphate ester fire-resistant oil, and prevent moisture from accelerating the hydrolysis and degradation of the oil. The decolorizing adsorbent is used to remove degradation products in the fire-resistant oil, and improve the color and transparency of the oil. The defoaming curing agent is used to eliminate foam in phosphate ester fire-resistant oil and prevent new foam from being generated, so as to prevent the foam from affecting the fluidity and hydraulic transmission efficiency of the oil. The composite adsorbent can simultaneously reduce the color, acid value and moisture of phosphate ester fire-resistant oil, and improve its resistivity; improve the dispersion effect of the defoaming agent in the fire-resistant oil, improve its anti-foaming and defoaming capabilities, and can effectively improve the use performance and life of phosphate ester fire-resistant oil, save resources, reduce costs, and improve the operation and maintenance efficiency of the unit, thereby improving the economy and stability of the generator set operation. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0024] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0025] It should also be understood that the terms used in the present specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the present specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.

[0026] It should be further understood that the term "and / or" used in the present description and the appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0027] The first object of the present invention is to provide a composite adsorbent for improving the performance of phosphate fire-resistant oil, including a deacidifying adsorbent, a dehydrating adsorbent, a decolorizing adsorbent and a defoaming curing agent; wherein the dehydrating adsorbent accounts for 20wt% to 30wt%, which can not only ensure the dehydration effect, but also maintain a suitable system pressure; the defoaming curing agent accounts for no more than 5wt%, which is sufficient to dissipate the foam quickly, and at the same time can avoid problems such as agglomeration of the defoaming agent due to excessive addition.

[0028] The deacidifying adsorbent is used to remove polar aging products in phosphate ester fire-resistant oil, prevent polar aging products from accelerating oil degradation, and increase the service life of the oil. The dehydrating adsorbent is used to remove moisture in phosphate ester fire-resistant oil, prevent moisture from accelerating the hydrolysis and degradation of the oil. The decolorizing adsorbent is used to remove degradation products in the fire-resistant oil, and improve the color and transparency of the oil. The defoaming curing agent is used to eliminate foam in phosphate ester fire-resistant oil and prevent new foam from being generated, so as to prevent foam from affecting the fluidity and hydraulic transmission efficiency of the oil. In summary, the composite adsorbent for improving the performance of phosphate ester fire-resistant oil of the present invention can comprehensively improve the quality of phosphate ester fire-resistant oil, improve its performance and life, and provide a strong guarantee for the stable operation of the system by integrating multiple functional adsorbents.

[0029] Before the composite adsorbent is used for adsorption treatment of phosphate fire-resistant oil, it needs to be dried at 150°C for 2h to 3h, and then added to the phosphate fire-resistant oil after it is cooled to room temperature; the use temperature of the composite adsorbent when used to treat phosphate fire-resistant oil is 40°C to 70°C.

[0030] The deacidification adsorbent includes a combination of one or more of silica-alumina adsorbent, activated alumina, activated magnesium oxide and diatomaceous earth; wherein, at least silica-alumina adsorbent is included, and when the deacidification adsorbent is a combination of multiple compositions, the proportion of silica-alumina adsorbent is not less than 70wt%; the size of each component particle in the deacidification adsorbent is 100μm to 150μm. Silica-alumina adsorbent, activated alumina, activated magnesium oxide and diatomaceous earth are all porous structures with high specific surface areas, which can effectively remove polar aging products in oil and reduce acid value.

[0031] The dehydration adsorbent includes a molecular sieve and a silica gel or a combination of both; the molecular sieve accounts for no less than 80 wt % of the composition. The molecular sieve and silica gel have regular microporous channel structures and large specific surface areas, so that the molecular sieve can efficiently adsorb water molecules.

[0032] The decolorizing adsorbent includes one or more combinations of activated carbon, silicon-aluminum adsorbent and activated magnesium oxide; wherein at least activated carbon is included, and when the decolorizing adsorbent is a combination of multiple combinations, the proportion of activated carbon is not higher than 15wt%; the size of the silicon-aluminum adsorbent and activated magnesium oxide in the decolorizing adsorbent is 100μm to 150μm; the size of the activated carbon is 150μm to 200μm. Activated carbon, silicon-aluminum adsorbent and activated magnesium oxide can efficiently adsorb various degradation products that deepen the color of oil due to their porous structure and large specific surface area.

[0033] The defoaming curing agent is a composite of a defoaming agent and activated carbon, which can release the defoaming agent during the oil treatment process, help the defoaming agent to be better released and dispersed in the oil system, reduce agglomeration, and improve defoaming efficiency.

[0034] The second object of the present invention is to provide a method for using a composite adsorbent for improving the performance of phosphate fire-resistant oils, comprising the following steps:

[0035] The deacidification adsorbent, the dehydration adsorbent and the decolorization adsorbent are dried and mixed with a defoaming curing agent to obtain a composite adsorbent, and the composite adsorbent is added into the fire-resistant oil to be treated;

[0036] The preparation method of the defoaming curing agent is as follows: 1 part (by volume) of the defoaming agent is added to 10 parts of petroleum ether or anhydrous ethanol, and stirred at 30°C to 40°C for 1h to 3h, with a stirring speed of 700r / min to 800r / min, to obtain a uniformly mixed dilution. Activated carbon having a volume of one-half of the dilution is added to the dilution, and ultrasonically vibrated at 30°C to 40°C for 1h to 3h; after the vibration, the activated carbon is placed in an oven at a temperature of 100°C to 105°C, and dried for 2h to 3h to obtain the defoaming curing agent.

[0037] The pore size of the outer channel of the activated carbon is not less than 2000nm; the activated carbon is coal-based activated carbon, wood-based activated carbon or fruit shell activated carbon, and mainly serves as a defoaming agent carrier.

[0038] The particle size of the defoamer is no more than 1000 nm; the defoamer is a polyether defoamer or a silicone defoamer.

[0039] Example 1

[0040] SA-02 silicon-aluminum adsorbent was selected as deacidification adsorbent, 4A-H molecular sieve was selected as dehydration adsorbent, ZM-150 activated magnesium oxide and Z-301 activated carbon were selected as decolorization adsorbents, and the defoaming curing agent was a composite of G005 fruit shell activated carbon and DT-06 polyether defoaming agent, wherein the mass proportion of the deacidification adsorbent was 50wt%, the mass proportion of the dehydration adsorbent was 20wt%, the mass proportion of the decolorization adsorbent was 25wt% (the mass of Z-301 activated carbon was 15wt% of the decolorization adsorbent), and the mass proportion of the defoaming curing agent was 5wt%. Among them, the particle size of SA-02 silicon-aluminum adsorbent was 100μm, the particle size of ZM-150 activated magnesium oxide and Z-301 activated carbon was 150μm, the pore size of the outer channel of G005 fruit shell activated carbon was 2000nm, and the particle size of DT-06 polyether defoaming agent was 1000nm.

[0041] 50 mL of DT-06 polyether defoamer was added to 500 mL of anhydrous ethanol and stirred at 35°C for 1 h at a stirring speed of 700 r / min to obtain a uniformly mixed dilution. 275 mL of macroporous activated carbon was added to the dilution and ultrasonically vibrated at 35°C for 1 h. After the vibration, the macroporous activated carbon was placed in an oven at 100°C and dried for 2 h to obtain a defoaming curing agent.

[0042] The deacidification adsorbent, the dehydration adsorbent and the decolorization adsorbent are dried and then mixed with a defoaming curing agent to obtain a composite adsorbent.

[0043] The composite adsorbent was used to # 1 Unit operation # 46 Phosphate fire-resistant oil was subjected to adsorption treatment, the adsorbent dosage was 4wt%, and the treatment process was as follows:

[0044] The composite adsorbent was dried at 150°C for 2 hours and then cooled to room temperature, and 40.0 g of it was added to 1000.0 g of the fire-resistant oil to be treated. The fire-resistant oil was stirred and adsorbed at 60°C for 2 hours at a stirring speed of 800 r / min, and then filtered with qualitative filter paper, and the filtered fire-resistant oil was collected.

[0045] The key indicators of the fire-resistant oil before and after treatment, such as color, acid value, resistivity, moisture and foam properties, were tested. The test methods are as follows: the color determination method is DL / T429.2 "Color determination method for power oil", the acid value determination method is GB / T264 "Acid value determination method for petroleum products", the resistivity determination method is DL / T421-2009 "Volume resistivity determination method for power oil", the moisture determination method is GB / T7600-2014 "Determination of moisture content of transformer oil and turbine oil in operation (coulometric method)", and the foam property determination method is GB / T12579-2002 "Determination of foam properties of lubricating oil". The indicators of fire-resistant oil before and after adsorption treatment are shown in Table 1.

[0046] Table 1 A power plant in Shaanxi # 1 Unit operation # 46 Oil quality indicators before and after phosphate ester fire-resistant oil treatment

[0047]

[0048] From the changes in the indicators of fire-resistant oil in Table 1, it can be seen that a small amount of composite adsorbent can simultaneously reduce the color, acid value and moisture content of phosphate fire-resistant oil, increase its resistivity, and improve its anti-foaming and defoaming capabilities, thereby improving the performance and life of phosphate fire-resistant oil.

[0049] Example 2

[0050] TK-01 silica-alumina adsorbent and MH-005 activated magnesium oxide were selected as deacidification adsorbents, 3A-H molecular sieve and ZK205 silica gel were selected as dehydration adsorbents, GK-05 silica-alumina adsorbent and Z-101 activated carbon were selected as decolorization adsorbents, and the defoaming curing agent was a composite of G009 fruit shell activated carbon and KN-02 silicone defoaming agent, wherein the mass proportion of the deacidification adsorbent was 40wt% (the mass of TK-01 silica-alumina adsorbent was 70wt% of the deacidification adsorbent), the mass proportion of the dehydration adsorbent was 30wt% (the mass of 3A-H molecular sieve was 80wt% of the dehydration adsorbent), the mass proportion of the decolorization adsorbent was 25wt% (the mass of Z-101 activated carbon was 10wt% of the decolorization adsorbent), and the mass proportion of the defoaming curing agent was 5wt%. Among them, the particle size of the deacidification adsorbent is 150μm, the particle size of the GK-05 type silicon-aluminum adsorbent is 150μm, the particle size of the Z-301 activated carbon is 200μm, the outer channel pore size of the G009 type fruit shell activated carbon is 2500nm, and the particle size of the KN-02 type silicone defoamer is 900nm.

[0051] Add 50mL of KN-02 silicone defoamer to 500mL of petroleum ether with a boiling point of 60℃~90℃, and stir at 30℃ for 3h at a stirring speed of 800r / min to obtain a uniformly mixed dilution. Add 275mL of G009 activated carbon to the dilution and ultrasonically vibrate at 30℃ for 3h. After the vibration, place the G009 fruit shell activated carbon in an oven at 105℃ and dry for 2h to obtain a defoaming curing agent.

[0052] The deacidification adsorbent, the dehydration adsorbent and the decolorization adsorbent are dried and then mixed with a defoaming curing agent to obtain a composite adsorbent.

[0053] The composite adsorbent was used to # 3 Unit operation # 46 Phosphate fire-resistant oil was subjected to adsorption treatment, the adsorbent dosage was 5wt%, and the treatment process was as follows:

[0054] The composite adsorbent was dried at 150°C for 2.5 hours and then cooled to room temperature, and 50.0 g of it was added to 1000.0 g of the fire-resistant oil to be treated. The fire-resistant oil was stirred and adsorbed at 70°C for 2 hours at a stirring speed of 900 r / min, and then filtered with qualitative filter paper, and the filtered fire-resistant oil was collected.

[0055] Key indicators of the fire-resistant oil before and after treatment, such as color, acid value, resistivity, moisture and foam properties, were tested. The fire-resistant oil indicators before and after adsorption treatment are shown in Table 2.

[0056] Table 2 A power plant in Hunan # 3 Unit operation # 46 Oil quality indicators before and after phosphate ester fire-resistant oil treatment

[0057]

[0058] From the changes in the indicators of the fire-resistant oil in Table 2, it can be seen that a small amount of composite adsorbent can simultaneously and effectively reduce the color, acid value and moisture content of phosphate ester fire-resistant oil, increase its resistivity, and improve its anti-foaming and defoaming capabilities, thereby improving the performance and life of phosphate ester fire-resistant oil.

[0059] Example 3

[0060] GP-100 silicon-aluminum adsorbent was selected as deacidification adsorbent, 5A-N molecular sieve was selected as dehydration adsorbent, GM-05 activated magnesium oxide and VM-5 activated carbon were selected as decolorization adsorbents, and the defoaming curing agent was a composite of D50 wood activated carbon and GT-04 polyether defoaming agent, wherein the mass proportion of deacidification adsorbent was 60wt%, the mass proportion of dehydration adsorbent was 22wt%, the mass proportion of decolorization adsorbent was 15wt% (the mass of VM-5 activated carbon was 10wt% of the decolorization adsorbent), and the mass proportion of defoaming curing agent was 3wt%. Among them, the particle size of GP-100 silicon-aluminum adsorbent was 100μm, the particle size of GM-05 activated magnesium oxide was 100μm, the particle size of VM-5 activated carbon was 150μm, the outer channel pore size of D50 wood activated carbon was 2200nm, and the particle size of GT-04 polyether defoaming agent was 900nm.

[0061] 60 mL of GT-04 polyether defoamer was added to 600 mL of anhydrous ethanol and stirred at 40°C for 1 h at a stirring speed of 700 r / min to obtain a uniformly mixed dilution. 330 mL of D50 activated carbon was added to the dilution and ultrasonically vibrated at 40°C for 1 h. After the vibration, the D50 wood activated carbon was placed in an oven at 100°C and dried for 3 h to obtain a defoaming curing agent.

[0062] The deacidification adsorbent, the dehydration adsorbent and the decolorization adsorbent are dried and then mixed with a defoaming curing agent to obtain a composite adsorbent.

[0063] The composite adsorbent was used to # 1 Unit operation # 46 phosphate fire-resistant oil was subjected to adsorption treatment, the adsorbent dosage was 6wt%, and the treatment process was as follows:

[0064] The composite adsorbent was dried at 150°C for 3 hours and then cooled to room temperature, and 60.0 g of it was added to 1000.0 g of the fire-resistant oil to be treated. The fire-resistant oil was stirred and adsorbed at 40°C for 2 hours at a stirring speed of 800 r / min, and then filtered with qualitative filter paper, and the filtered fire-resistant oil was collected.

[0065] Key indicators of the fire-resistant oil before and after treatment, such as color, acid value, resistivity, moisture and foam properties, were tested. The fire-resistant oil indicators before and after adsorption treatment are shown in Table 3.

[0066] Table 3 A power plant in Shanghai # 1 Unit operation # 46 Oil quality indicators before and after phosphate ester fire-resistant oil treatment

[0067]

[0068]

[0069] From the changes in the indicators of the fire-resistant oil in Table 3, it can be seen that a small amount of composite adsorbent can simultaneously and effectively reduce the color, acid value and moisture content of phosphate ester fire-resistant oil, increase its resistivity, and improve its anti-foaming and defoaming capabilities, thereby improving the performance and life of phosphate ester fire-resistant oil.

[0070] Example 4

[0071] GP-100 silica-alumina adsorbent, MH-005 activated magnesium oxide and SD-05 diatomaceous earth were selected as deacidification adsorbents, ZK205 silica gel was used as dehydration adsorbent, VM-5 activated carbon, GK-05 silica-alumina adsorbent and ZM-150 activated magnesium oxide were used as decolorization adsorbents, and the defoaming curing agent was a composite of G005 fruit shell activated carbon and DT-06 polyether defoaming agent, wherein the mass proportion of the deacidification adsorbent was 50wt% (the mass of GP-100 silica-alumina adsorbent was 75wt% of the deacidification adsorbent, and the mass of MH-005 activated magnesium oxide was 15wt% of the deacidification adsorbent), the mass proportion of the dehydration adsorbent was 25wt%, the mass proportion of the decolorization adsorbent was 21wt% (the mass of ZM-150 activated magnesium oxide was 67wt% of the decolorization adsorbent, and the mass of VM-5 activated carbon was 13wt% of the decolorization adsorbent), and the mass proportion of the defoaming curing agent was 4wt%. Among them, the size of MH-005 activated magnesium oxide is 150μm, and the particle size of other deacidification adsorbents is 100μm; the size of decolorization adsorbent is 150μm; the pore size of the outer channel of G005 fruit shell activated carbon is 2000nm, and the particle size of DT-06 polyether defoamer is 1000nm.

[0072] 50 mL of DT-06 polyether defoamer was added to 500 mL of anhydrous ethanol and stirred at 35°C for 1 h at a stirring speed of 700 r / min to obtain a uniformly mixed dilution. 275 mL of macroporous activated carbon was added to the dilution and ultrasonically vibrated at 35°C for 1 h. After the vibration, the macroporous activated carbon was placed in an oven at 100°C and dried for 2 h to obtain a defoaming curing agent.

[0073] The deacidification adsorbent, the dehydration adsorbent and the decolorization adsorbent are dried and then mixed with a defoaming curing agent to obtain a composite adsorbent.

[0074] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A composite adsorbent for improving the performance of phosphate fire-resistant oil, characterized in that: It includes a deacidifying adsorbent, a dehydrating adsorbent, a decolorizing adsorbent and a defoaming curing agent, wherein the dehydrating adsorbent accounts for 20wt% to 30wt%, and the defoaming curing agent accounts for no more than 5wt%.

2. A composite adsorbent for improving the performance of phosphate fire-resistant oil according to claim 1, characterized in that: The deacidification adsorbent includes a silica-alumina adsorbent, and a composition of a silica-alumina adsorbent and one or more of activated alumina, activated magnesium oxide and diatomaceous earth; wherein at least a silica-alumina adsorbent is included, and when the deacidification adsorbent is a plurality of compositions, the proportion of the silica-alumina adsorbent is not less than 70wt%.

3. A composite adsorbent for improving the performance of phosphate fire-resistant oil according to claim 2, characterized in that: The size of each component particle in the deacidification adsorbent is 100 μm to 150 μm.

4. The composite adsorbent for improving the performance of phosphate fire-resistant oil according to claim 1, characterized in that: The dehydration adsorbent comprises a molecular sieve and silica gel, or a combination of both; the molecular sieve accounts for no less than 80 wt % of the composition.

5. The composite adsorbent for improving the performance of phosphate fire-resistant oil according to claim 1, characterized in that: The decolorizing adsorbent comprises at least two compositions selected from activated carbon, silicon-aluminum adsorbent and activated magnesium oxide; wherein when at least activated carbon is included, the proportion of activated carbon is not higher than 15wt%; Or the decolorizing adsorbent is a silicon-aluminum adsorbent or active magnesium oxide.

6. The composite adsorbent for improving the performance of phosphate fire-resistant oil according to claim 5, characterized in that: The sizes of the silicon-aluminum adsorbent and the activated magnesium oxide in the decolorizing adsorbent are 100 μm to 150 μm; and the size of the activated carbon is 150 μm to 200 μm.

7. The composite adsorbent for improving the performance of phosphate fire-resistant oil according to claim 1, characterized in that: The defoaming curing agent comprises activated carbon and a defoaming agent.

8. The composite adsorbent for improving the performance of phosphate fire-resistant oil according to claim 7, characterized in that: The pore size of the outer channel of the activated carbon is not less than 2000nm; the activated carbon is coal-based activated carbon, wood-based activated carbon or fruit shell activated carbon.

9. The composite adsorbent for improving the performance of phosphate fire-resistant oil according to claim 7, characterized in that: The particle size of the defoamer is no more than 1000 nm; the defoamer is a polyether defoamer or a silicone defoamer.

10. A method for using a composite adsorbent for improving the performance of phosphate fire-resistant oils, characterized in that: The following steps are involved: The deacidification adsorbent, the dehydration adsorbent and the decolorization adsorbent are dried and mixed with a defoaming curing agent to obtain a composite adsorbent, and the composite adsorbent is added into the fire-resistant oil to be treated; The preparation method of the defoaming curing agent is as follows: adding the defoaming agent to petroleum ether or anhydrous ethanol, stirring to obtain a uniformly mixed dilution; adding activated carbon with a volume of half the dilution to the dilution, after ultrasonic vibration, drying the activated carbon to obtain the defoaming curing agent.